2014
DOI: 10.1021/ic402539x
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of a Metal Complex within a Self-Assembled Nanocage: Synergy Effects, Molecular Structures, and Density Functional Theory Calculations

Abstract: A novel palladium-based metallacage was self-assembled. This nanocage displayed two complementary effects that operate in synergy for guest encapsulation. Indeed, a metal complex, [Pt(NO2)4](2-), was hosted inside the cavity, as demonstrated by solution NMR studies. Single-crystal X-ray diffraction shows that the guest adopts two different orientations, depending on the nature of the host-guest interactions involved. A density functional theory computational study is included to rationalize this type of host-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…This difference in binding strength between the p-toluenesulfonate and the benzoate provides interesting opportunities, as we can now functionalize the catalyst with the strong binding unit and the substrate with the weaker binding unit. Along these lines we evaluated the binding of gold complex TPPMSAuCl (TPPMS = triphenylphosphinomonosulfonate), and found that this complex was also fully encapsulated until precipitation was observed, as confirmed by NMR and DOSY (see Supplementary Figs 41-42 and 52) (for some examples of encapsulation of a metal complex within self-assembled M 2 L 4 nanocapsules, see Desmarets et al 31,32 ). The CSI-MS spectra of sphere 2 mixed with various amounts (6, 12, 18 and 24 equiv.)…”
Section: Resultsmentioning
confidence: 95%
“…This difference in binding strength between the p-toluenesulfonate and the benzoate provides interesting opportunities, as we can now functionalize the catalyst with the strong binding unit and the substrate with the weaker binding unit. Along these lines we evaluated the binding of gold complex TPPMSAuCl (TPPMS = triphenylphosphinomonosulfonate), and found that this complex was also fully encapsulated until precipitation was observed, as confirmed by NMR and DOSY (see Supplementary Figs 41-42 and 52) (for some examples of encapsulation of a metal complex within self-assembled M 2 L 4 nanocapsules, see Desmarets et al 31,32 ). The CSI-MS spectra of sphere 2 mixed with various amounts (6, 12, 18 and 24 equiv.)…”
Section: Resultsmentioning
confidence: 95%
“…[21][22][23][24][25][26] These architectures display high symmetry and are capable of encapsulating guests such as anions or organic molecules but to a lesser extent metal compounds. [27][28][29][30] They are usually obtained by mixing metal precursors displaying four available coordination sites and bidentate ligands. While Pd2L4 cages have been intensively described, surprisingly so far only a few platinum analogues have been reported.…”
Section: N Introductionmentioning
confidence: 99%
“…Host–guest chemistry of self-assembled coordination cages has attracted much attention in the past two decades. These cages can now be obtained with different shapes and display cavities with controllable sizes. As a consequence, a wide range of applications have been investigated including molecular sensing, chiral separation, drug delivery, and catalytic properties. Among these cages, particular interest has been devoted to the formation of the M 2 L 4 cage-type. These architectures display high symmetry and are capable of encapsulating guests such as anions or organic molecules but to a lesser extent metal compounds. They are usually obtained by mixing metal precursors displaying four available coordination sites and bidentate ligands. While Pd 2 L 4 cages have been intensively described, surprisingly, so far only a few platinum analogues have been reported. , …”
Section: Introductionmentioning
confidence: 99%
“…Several reviews have thoroughly covered this amazing field in the last years [31][32][33][34][35][36][37][38][39]. The inherent stability and rather low reactivity of the Pt(II) in contrast with other metals [i.e., Pd(II)] [40,41] has been the main attraction for the use of Pt(II) units for metallamacrocycles [42]. Furthermore, the attractive photophysical properties of Pt(II) complexes, such as low-energy, tunability and long-lived excited states, have prompted their incorporation into metallacycles [43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%